La formation professionnelle initiale duale comme levier d’engagement organisationnel : analyse d’un dispositif de formation d’apprenti-es assistant-es en soins et santé communautaire (ASSC) dans le contexte domiciliaire - Camille Crottaz; Nathalie Delobbe; Sandrine Fellay Morante (Éducation et Socialisation)
Referring mainly to the organizational socialization theories, this article focuses on a vocational apprenticeship training program at the upper secondary level for healthcare and community health assistant. It explores the influence of the on-the-job training practices on the retention of the apprentices in the training company. This contribution puts forward a broader vision of the spectrum of learning, considering both the processes of acquisition of vocational skills and the socializing dimension of training practices. The interviews conducted in a home care institution highlight two key elements of on-the-job training that affect the organizational socialization process: the definition of the job and the activities entrusted to the apprentices, on the one hand, and the extended relational circle to which they have access, on the other.